Polyacrylonitrile-based carbon fiber as well as preparation method and application thereof
By performing multi-step carbonization and graphitization on polyacrylonitrile-based fibers, polyacrylonitrile-based carbon fibers with high tensile modulus and high tensile strength were prepared, which solved the problem that existing carbon fiber materials could not achieve high modulus and high strength at the same time, and achieved its wide application in composite materials.
Patent Information
- Application Number
- CN202510015281.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing carbon fiber materials cannot achieve high tensile modulus and high tensile strength at the same time, limiting their application in composite materials.
By performing multi-step treatment of pre-oxidation, low-temperature carbonization, alkali leaching, high-temperature carbonization and graphitization of the polyacrylonitrile-based fibers, polyacrylonitrile-based carbon fibers with tensile modulus of 200 to 590 GPa were prepared.
The tensile modulus and tensile strength of carbon fiber are improved, making it suitable for scenarios with high mechanical performance requirements, such as aerospace, automotive materials, sports equipment and wind power generation.
Smart Images

Figure CN119753892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fibers, and in particular relates to a polyacrylonitrile-based carbon fiber and a preparation method and application thereof. Background Art
[0002] Carbon fiber, a fiber material with a carbon content of more than 90%, has the characteristics of small thermal expansion coefficient, strong tensile properties, corrosion resistance, high conductivity, high temperature resistance, fatigue resistance and low density. It is widely used in aerospace, automotive materials, sports equipment and wind power generation.
[0003] Carbon fiber is mainly divided into two categories: high-strength carbon fiber and high-modulus carbon fiber. At present, the tensile strength of high-strength carbon fiber is above 3.5GPa, but the tensile modulus is relatively small; the tensile modulus of high-modulus carbon fiber is above 300GPa, but the tensile strength is relatively small. High-strength carbon fiber cannot achieve high modulus, and similarly, high-modulus carbon fiber cannot achieve high strength.
[0004] High modulus carbon fiber can be used to increase the elastic modulus of composite materials. At present, the carbon fiber with the highest modulus in the world is the M60J carbon fiber produced by Toray of Japan, with a tensile modulus of 588GPa. How to further improve the modulus of carbon fiber materials is an urgent problem to be solved in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a polyacrylonitrile-based carbon fiber and a preparation method and application thereof. The tensile modulus of the polyacrylonitrile-based carbon fiber obtained by the preparation method provided by the present invention is 200 to 590 GPa.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0008] The polyacrylonitrile-based fiber is sequentially subjected to pre-oxidation, low-temperature carbonization, alkali leaching, high-temperature carbonization and graphitization to obtain the polyacrylonitrile-based carbon fiber; the temperature of the low-temperature carbonization is 300-800°C; the reagent for the alkali leaching is an aqueous solution of a metal catalyst; the temperature of the high-temperature carbonization is 1200-1500°C; the temperature of the graphitization is 2000-2500°C.
[0009] Preferably, the pre-oxidation is a segmented pre-oxidation; the segmented pre-oxidation includes sequentially performing a first pre-oxidation, a second pre-oxidation, a third pre-oxidation, a fourth pre-oxidation, a fifth pre-oxidation and a sixth pre-oxidation; the temperature of the first pre-oxidation is 230-245°C, and the holding time is 10-20 min; the temperature of the second pre-oxidation is 240-255°C, and the holding time is 10-20 min; the temperature of the third pre-oxidation is 250-265°C, and the holding time is 10-20 min; the temperature of the fourth pre-oxidation is 260-275°C, and the holding time is 10-20 min; the temperature of the fifth pre-oxidation is 270-285°C, and the holding time is 10-20 min; the temperature of the sixth pre-oxidation is 280-295°C, and the holding time is 10-20 min; the total stretching ratio of the pre-oxidation is 2-8%.
[0010] Preferably, the first pre-oxidation temperature is 230-240°C; the second pre-oxidation temperature is 240-250°C; the third pre-oxidation temperature is 250-260°C; the fourth pre-oxidation temperature is 260-270°C; the fifth pre-oxidation temperature is 270-280°C; the sixth pre-oxidation temperature is 280-295°C; and the total stretching ratio of the pre-oxidation is 2-6%.
[0011] Preferably, the low-temperature carbonization is segmented low-temperature carbonization; the segmented low-temperature carbonization includes sequentially performing a first low-temperature carbonization, a second low-temperature carbonization, a third low-temperature carbonization and a fourth low-temperature carbonization; the temperature of the first low-temperature carbonization is 300-400°C, and the insulation carbonization time is 3-5 min; the temperature of the second low-temperature carbonization is 500-600°C, and the insulation carbonization time is 3-5 min; the temperature of the third low-temperature carbonization is 600-800°C, and the insulation carbonization time is 3-5 min; the temperature of the fourth low-temperature carbonization is 500-600°C, and the insulation carbonization time is 3-5 min; the total stretching ratio of the low-temperature carbonization is -7 to -1%.
[0012] Preferably, the temperature of the first low-temperature carbonization is 380-400°C; the temperature of the second low-temperature carbonization is 550-600°C; the temperature of the third low-temperature carbonization is 750-800°C; the temperature of the fourth low-temperature carbonization is 580-600°C.
[0013] Preferably, the high-temperature carbonization is segmented high-temperature carbonization; the segmented high-temperature carbonization includes sequentially performing a first high-temperature carbonization and a second high-temperature carbonization; the temperature of the first high-temperature carbonization is 1200-1300°C, and the insulation time is 1-4 min; the temperature of the second high-temperature carbonization is 1300-1600°C, and the insulation time is 1-4 min; the total stretching ratio of the high-temperature carbonization is -5-1%.
[0014] Preferably, the high-temperature carbonization is a four-stage high-temperature carbonization; the four-stage high-temperature carbonization includes a third high-temperature carbonization, a fourth high-temperature carbonization, a fifth high-temperature carbonization and a sixth high-temperature carbonization in sequence; the temperature of the third high-temperature carbonization is 1000-1200°C, and the insulation carbonization time is 1-2.5 min; the temperature of the fourth high-temperature carbonization is 1200-1400°C, and the insulation carbonization time is 1-2.5 min; the temperature of the fifth high-temperature carbonization is 1400-1600°C, and the insulation carbonization time is 1-2.5 min; the temperature of the sixth high-temperature carbonization is 1600-1800°C, and the insulation carbonization time is 1-2.5 min; the total stretching ratio of the four-stage high-temperature carbonization is -7-0.5%.
[0015] Preferably, the graphitization includes a first graphitization and a second graphitization performed sequentially; the temperature of the first graphitization is 2000-2200°C, and the insulation graphitization time is 10-85s; the temperature of the second graphitization is 2300-2500°C, and the insulation graphitization time is 10-135s; the total stretching ratio of the graphitization is -1-7%.
[0016] The present invention also provides polyacrylonitrile-based carbon fibers obtained by the preparation method described in the above scheme.
[0017] The present invention also provides the application of the polyacrylonitrile-based carbon fiber described in the above scheme in the fields of aerospace, automotive materials, sports equipment or wind power generation.
[0018] The present invention provides a method for preparing polyacrylonitrile-based carbon fiber. The preparation method provided by the present invention improves the tensile modulus of polyacrylonitrile-based carbon fiber, and the tensile modulus is between 200 and 590 GPa, and the tensile strength is above 2.4 GPa. The present invention promotes the formation of a graphite-like structure of carbon fiber (elimination of non-graphite carbon) and the improvement of its regularity through the gasification reaction of a metal catalyst, removes elements other than carbon, and through low-temperature graphitization, the plane of the graphite layer is further oriented along the fiber axis, the rigidity of the molecular chain becomes larger, the modulus is improved, and at the same time, the problems of large amount of fuzz and high energy consumption of carbon fiber during graphitization are effectively alleviated.
[0019] The present invention also provides polyacrylonitrile-based carbon fibers obtained by the preparation method described in the above scheme. The polyacrylonitrile-based carbon fibers provided by the present invention have high tensile modulus, which is between 200 and 590 GPa, good tensile strength, which is above 2.4 GPa, and excellent comprehensive mechanical properties.
[0020] The present invention also provides the application of the polyacrylonitrile-based carbon fiber described in the above scheme in the fields of aerospace, automotive materials, sports equipment or wind power generation. The polyacrylonitrile-based carbon fiber provided by the present invention has a high tensile modulus and is suitable for use in scenarios requiring high mechanical properties, such as aerospace, automotive materials, sports equipment or wind power generation, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 is a cross-sectional view of the polyacrylonitrile-based carbon fiber of Example 2;
[0023] Figure 2 is a cross-sectional view of the polyacrylonitrile-based carbon fiber of Example 1;
[0024] Figure 3 is a cross-sectional view of the polyacrylonitrile-based carbon fiber of Example 15;
[0025] Figure 4 This is a cross-sectional view of the polyacrylonitrile-based carbon fiber of Example 14. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0027] The polyacrylonitrile-based fiber is sequentially subjected to pre-oxidation, low-temperature carbonization, alkali leaching, high-temperature carbonization and graphitization to obtain the polyacrylonitrile-based carbon fiber; the temperature of the low-temperature carbonization is 300-800°C; the reagent for the alkali leaching is an aqueous solution of a metal catalyst; the temperature of the high-temperature carbonization is 1200-1500°C; the temperature of the graphitization is 2000-2500°C.
[0028] The present invention pre-oxidizes the polyacrylonitrile-based fiber. In the present invention, the polyacrylonitrile-based fiber is preferably prepared by a wet method or a dry-wet method; the tow of the polyacrylonitrile-based fiber is preferably 1 to 46K, specifically 1K, 3K, 6K, 12K, 18K, 24K, 30K, 36K or 46K. The present invention uses polyacrylonitrile as a raw material, which helps to reduce the cost of carbon fiber and improve the performance of carbon fiber.
[0029] In the present invention, the pre-oxidation is preferably staged pre-oxidation; the staged pre-oxidation preferably includes sequentially performing a first pre-oxidation, a second pre-oxidation, a third pre-oxidation, a fourth pre-oxidation, a fifth pre-oxidation and a sixth pre-oxidation.
[0030] In the present invention, the temperature of the first pre-oxidation is preferably 230-245°C, specifically 230°C, 232°C, 234°C, 236°C, 238°C, 240°C, 242°C or 245°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0031] In the present invention, the temperature of the second pre-oxidation is preferably 240-255°C, specifically 240°C, 242°C, 244°C, 246°C, 248°C, 250°C, 252°C or 255°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0032] In the present invention, the temperature of the third pre-oxidation is preferably 250-265°C, specifically 250°C, 252°C, 254°C, 256°C, 258°C, 260°C, 262°C or 265°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0033] In the present invention, the temperature of the fourth pre-oxidation is preferably 260-275°C, specifically 260°C, 262°C, 264°C, 266°C, 268°C, 270°C, 272°C or 275°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0034] In the present invention, the temperature of the fifth pre-oxidation is preferably 270-285°C, specifically 270°C, 272°C, 274°C, 276°C, 278°C, 280°C, 282°C or 285°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0035] In the present invention, the temperature of the sixth pre-oxidation is preferably 280-295°C, specifically 280°C, 282°C, 284°C, 286°C, 288°C, 290°C, 292°C or 295°C, and the insulation time is preferably 10-20min, specifically 10min, 12min, 14min, 16min, 18min or 20min.
[0036] In the present invention, the pre-oxidation is preferably carried out in an air atmosphere.
[0037] In the present invention, the total draft ratio of the pre-oxidation is preferably 2-8%, specifically 2%, 3%, 4%, 5%, 6%, 7% or 8%.
[0038] The present invention controls the conditions of the segmented pre-oxidation to be 230-240°C for the first pre-oxidation, 240-250°C for the second pre-oxidation, 250-260°C for the third pre-oxidation, 260-270°C for the fourth pre-oxidation, 270-280°C for the fifth pre-oxidation and 280-295°C for the sixth pre-oxidation, and the total draft ratio is controlled at 2-6%. The oxygen content of the pre-oxidized fiber prepared thereby is 10-15%, and the bulk density is 1.33-1.45 g / cm 3 The crystallinity is between 22% and 30%, the tensile strength of a single fiber is between 1.3 and 2.2 cN / dtex, and the final polyacrylonitrile-based carbon fiber has high strength, with a strength of between 3 and 6.9 GPa.
[0039] After pre-oxidation, the pre-oxidized fiber is obtained, and the present invention performs low-temperature carbonization on the pre-oxidized fiber. In the present invention, the low-temperature carbonization is preferably staged low-temperature carbonization; the staged low-temperature carbonization preferably includes sequentially performing a first low-temperature carbonization, a second low-temperature carbonization, a third low-temperature carbonization and a fourth low-temperature carbonization.
[0040] In the present invention, the temperature of the first low-temperature carbonization is preferably 300-400°C, specifically 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, and the insulation carbonization time is preferably 3-5min, specifically 3min, 3.5min, 4min, 4.5min or 5min.
[0041] In the present invention, the temperature of the second low-temperature carbonization is preferably 500-600°C, specifically 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, and the insulation carbonization time is preferably 3-5min, specifically 3min, 3.5min, 4min, 4.5min or 5min.
[0042] In the present invention, the temperature of the third low-temperature carbonization is preferably 600-800°C, specifically 600°C, 640°C, 670°C, 700°C, 720°C, 750°C, 770°C or 800°C, and the insulation carbonization time is preferably 3-5min, specifically 3min, 3.5min, 4min, 4.5min or 5min.
[0043] In the present invention, the temperature of the fourth low-temperature carbonization is preferably 500-600°C, specifically 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, and the insulation carbonization time is preferably 3-5min, specifically 3min, 3.5min, 4min, 4.5min or 5min.
[0044] In the present invention, the low-temperature carbonization is preferably carried out in a nitrogen atmosphere or a helium atmosphere; the purity of the nitrogen or helium is preferably independently above 99.99%; and the equipment for the low-temperature carbonization is preferably a low-temperature carbonization furnace.
[0045] In the present invention, the total drawing ratio of the low-temperature carbonization is preferably -7 to -1%, specifically -1%, -2%, -3%, -4%, -5%, -6% or -7%.
[0046] The present invention controls the conditions of low-temperature carbonization at 380-400°C for the first low-temperature carbonization, 550-600°C for the second low-temperature carbonization, 750-800°C for the third low-temperature carbonization, and 580-600°C for the fourth low-temperature carbonization. The carbon content of the preliminary carbonized fiber prepared thereby is 70.56-78.77%, the oxygen content is 70-80%, the bulk density is 1.55-1.68%, the crystallinity is 30-37%, the tensile strength of a single fiber is 10-14 cN / dtex, and the polyacrylonitrile-based carbon fiber finally obtained has high strength, and its strength is 3-6.9 GPa. The present invention strictly controls the carbon content, oxygen content and crystallinity of the fiber obtained by pre-oxidation and low-temperature carbonization to improve the strength of the final carbon fiber.
[0047] After low-temperature carbonization, preliminary carbonized fibers are obtained, and the preliminary carbonized fibers are alkali-leached in the present invention. In the present invention, the alkali-leaching time is preferably 3 to 10 seconds, specifically 3 seconds, 4 seconds, 5 seconds, 6 seconds, 7 seconds, 8 seconds, 9 seconds or 10 seconds.
[0048] In the present invention, the alkali leaching reagent is an aqueous solution of a metal catalyst; the concentration of the aqueous solution of the metal catalyst is preferably not more than 1.5wt%, specifically 1.5wt%, 1.2wt%, 1.1wt%, 1.0wt%, 0.8wt%, 0.6wt%, 0.5wt%, 0.3wt% or 0.1wt%; the metal catalyst preferably includes one or more of a metal hydroxide and a metal carbonate.
[0049] In the present invention, the metal hydroxide preferably includes one or more of alkali metal hydroxides and alkaline earth metal hydroxides; the alkali metal hydroxide preferably includes one or both of KOH and NaOH; the alkaline earth metal hydroxide preferably includes one or both of Ca(OH)2 and Mg(OH)2.
[0050] In the present invention, the metal carbonate preferably includes one or more of alkali metal carbonate and alkaline earth metal carbonate; the alkali metal carbonate preferably includes one or more of Na2CO3 and K2CO3; the alkaline earth metal carbonate preferably includes one or more of MgCO3 and CaCO3. When the present invention does not perform alkali leaching, the strength performance of the finally obtained polyacrylonitrile-based carbon fiber is better, and the modulus performance is worse.
[0051] After alkali leaching, alkali-impregnated fibers are obtained, and the present invention performs high-temperature carbonization on the alkali-impregnated fibers. In the present invention, the high-temperature carbonization is preferably staged high-temperature carbonization; the staged high-temperature carbonization preferably includes sequentially performing a first high-temperature carbonization and a second high-temperature carbonization.
[0052] In the present invention, the temperature of the first high-temperature carbonization is preferably 1200-1300°C, specifically 1200°C, 1220°C, 1240°C, 1260°C, 1280°C or 1300°C, and the insulation time is preferably 1-4min, specifically 1min, 1.5min, 2min, 2.5min, 3min, 3.5min or 4min.
[0053] In the present invention, the temperature of the second high-temperature carbonization is preferably 1300-1600°C, specifically 1300°C, 1340°C, 1370°C, 1400°C, 1430°C, 1470°C, 1500°C, 1530°C, 1570°C or 1600°C, and the insulation time is preferably 1-4 min, specifically 1 min, 1.5 min, 2 min, 2.5 min, 3 min, 3.5 min or 4 min.
[0054] In the present invention, the high-temperature carbonization is preferably carried out in a helium atmosphere or a nitrogen atmosphere; the purity of the nitrogen or helium is preferably above 99.99%.
[0055] In the present invention, the total stretching ratio of the high temperature carbonization is preferably -5 to 1%, specifically -5%, -4.5%, -4%, -3.5%, -3%, -2.5%, -2%, -1.5%, -1%, 0.5% or 1%.
[0056] In the present invention, the high-temperature carbonization is more preferably a four-stage high-temperature carbonization; the four-stage high-temperature carbonization preferably includes a third high-temperature carbonization, a fourth high-temperature carbonization, a fifth high-temperature carbonization and a sixth high-temperature carbonization in sequence; the temperature of the third high-temperature carbonization is preferably 1000-1200°C, specifically 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, and the insulation carbonization time is preferably 1-2.5min, specifically 1.5min or 2min; the temperature of the fourth high-temperature carbonization is preferably 1200-1400°C, specifically 1200°C, 1250°C, 1300°C, 1350°C or 1400°C, and the insulation carbonization time is preferably 1-2.5min, specifically 1.5min or 2min; the fifth high-temperature carbonization is preferably 1200-1400°C, specifically 1200°C, 1250°C, 1300°C, 1350°C or 1400°C, and the insulation carbonization time is preferably 1-2.5min, specifically 1.5min or 2min; The temperature of the sixth high-temperature carbonization is preferably 1400-1600°C, specifically 1400°C, 1450°C, 1500°C, 1550°C or 1600°C, and the insulation carbonization time is preferably 1-2.5min, specifically 1.5min or 2min; the temperature of the sixth high-temperature carbonization is preferably 1600-1800°C, specifically 1600°C, 1650°C, 1700°C, 1750°C or 1800°C, and the insulation carbonization time is preferably 1-2.5min, specifically 1.5min or 2min; the total draw ratio of the third high-temperature carbonization, the fourth high-temperature carbonization, the fifth high-temperature carbonization and the sixth high-temperature carbonization is preferably -7-0.5%, specifically -7%, -6%, -5%, -4%, -3%, -2%, -1% or 0.5%. The present invention uses four-stage high-temperature carbonization to prepare carbonized fibers with a carbon content of 92.01-99.35%, a crystallinity of 38-42%, a strength of 3-7 GPa, and an elastic modulus of 200-400 GPa. The final polyacrylonitrile-based carbon fibers have high strength of 3-6.9 GPa.
[0057] After obtaining carbonized fibers through high-temperature carbonization, the present invention graphitizes the carbonized fibers. In the present invention, the graphitization preferably includes a first graphitization and a second graphitization performed sequentially.
[0058] In the present invention, the temperature of the first graphitization is preferably 2000-2200°C, specifically 2000°C, 2050°C, 2100°C, 2150°C or 2200°C, and the insulation graphitization time is preferably 10-85s, specifically 10s, 15s, 20s, 25s, 35s, 45s, 55s, 65s, 75s or 85s.
[0059] In the present invention, the temperature of the second graphitization is preferably 2300-2500°C, specifically 2300°C, 2350°C, 2400°C, 2450°C or 2500°C, and the insulation graphitization time is preferably 10-135s, specifically 10s, 20s, 30s, 40s, 50s, 70s, 90s, 110s, 130s or 135s.
[0060] In the present invention, the graphitization is preferably carried out in a helium atmosphere or a nitrogen atmosphere; the purity of the helium or nitrogen is preferably above 99.99%; and the graphitization equipment is preferably a graphitization furnace.
[0061] In the present invention, the total drawing ratio of graphitization is preferably -1 to 7%, specifically -1%, 1%, 2%, 3%, 4%, 5%, 6% or 7%.
[0062] In the preparation process of the present invention, the bulk density of the obtained pre-oxidized fiber is 1.38-1.45 g / cm 3 ; The carbon content of carbonized fiber is 94-97%, and the bulk density is 1.89-1.97g / cm 3 The carbon content of polyacrylonitrile-based carbon fiber is 97-99%, and the bulk density is 2.0-2.5 g / cm 3 In addition, the present invention further optimizes specific parameters, adjusts the uniformity of the internal structure of the carbon fiber, improves the stacking regularity of the graphite layer, promotes the formation of a graphite-like structure, removes a large amount of nitrogen and oxygen, and increases the carbon content, thereby preparing a high-strength polyacrylonitrile-based carbon fiber.
[0063] The present invention also provides polyacrylonitrile-based carbon fibers obtained by the preparation method described in the above scheme.
[0064] In the present invention, the carbon content of the polyacrylonitrile-based carbon fiber is above 94%, the crystallinity is above 35%, and the bulk density is above 1.8 g / cm 3 above.
[0065] The polyacrylonitrile-based carbon fiber provided by the present invention has a high tensile modulus of 200 to 590 GPa, a good tensile strength of more than 2.4 GPa, and excellent comprehensive mechanical properties.
[0066] The present invention also provides the application of the polyacrylonitrile-based carbon fiber described in the above scheme in the fields of aerospace, automotive materials, sports equipment or wind power generation.
[0067] The polyacrylonitrile-based carbon fiber provided by the present invention has a high tensile modulus and is suitable for use in scenarios requiring high mechanical properties, such as aerospace, automotive materials, sports equipment or wind power generation, and has broad application prospects.
[0068] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0069] In a specific embodiment of the present invention, the fiber element composition is detected by a German element analyzer, the crystallinity is detected by a wide-angle X-ray diffraction analyzer, the tensile strength of a single fiber is detected by a fiber strength and elongation meter, the fiber density is detected according to the GB / T 30019-2013 standard, and the tensile strength is detected according to the GB / T 3362-2017 standard.
[0070] Example 1
[0071] 3K polyacrylonitrile-based fiber (comonomers include acrylonitrile, methyl acrylate and itaconic acid) was used. In the pre-oxidation stage, a draft ratio of 4% was applied to the polyacrylonitrile-based fiber. Pre-oxidation was carried out in 6 temperature zones, which were 240°C for 10 min, 250°C for 10 min, 260°C for 10 min, 270°C for 10 min, 280°C for 10 min, and 295°C for 10 min. Low-temperature carbonization was carried out in 4 temperature zones, which were 390°C for 3 min, 590°C for 3 min. , 760℃ for 3min, 600℃ for 3min, with a total draft ratio of -6%; alkali immersion in K2CO3 aqueous solution (concentration of 0.2wt%) for 6s; high temperature carbonization through two temperature zones, 1300℃ for 1.5min, 1500℃ for 1.5min, with a total draft ratio of -6%; graphitization stage through two temperature zones of graphitization furnace, 2100℃ for 40s, 2200℃ for 40s, with a total draft ratio of -1%, to obtain polyacrylonitrile-based carbon fiber, its cross section is as follows Figure 2 shown.
[0072] Example 2
[0073] The preparation method of this embodiment is the same as that of embodiment 1, except that the total drawing ratio of graphitization is 1%, and other conditions are the same as those of embodiment 1. The cross section of the obtained polyacrylonitrile-based carbon fiber is as follows: Figure 1 As shown. Figure 1 and Figure 2 It can be seen that the cross-section of polyacrylonitrile-based carbon fibers with higher modulus is more neatly fractured, and the difference between the skin and the core is smaller.
[0074] Example 3
[0075] The preparation method of this embodiment is the same as that of embodiment 1, except that the total drawing ratio of graphitization is 5%, and other conditions are the same as those of embodiment 1.
[0076] Example 4
[0077] The preparation method of this embodiment is the same as that of embodiment 2, except that the concentration of the K2CO3 aqueous solution is 0.5wt%, and the other conditions are the same as those of embodiment 2.
[0078] Example 5
[0079] The preparation method of this embodiment is the same as that of embodiment 2, except that the concentration of the K2CO3 aqueous solution is 0.8wt%, and the other conditions are the same as those of embodiment 2.
[0080] Example 6
[0081] The preparation method of this embodiment is the same as that of embodiment 2, except that the concentration of the K2CO3 aqueous solution is 1wt%, and the other conditions are the same as those of embodiment 2.
[0082] Example 7
[0083] The preparation method of this embodiment is the same as that of Example 2, except that the concentration of the K2CO3 aqueous solution is 1.5wt%, and the other conditions are the same as those of Example 2.
[0084] The tensile strength and tensile modulus of the polyacrylonitrile-based carbon fibers prepared in Examples 1 to 7 were tested according to the GB / T 3362-2017 standard. The results are shown in Table 1.
[0085] Table 1 Tensile strength and tensile modulus of polyacrylonitrile-based carbon fibers prepared in Examples 1 to 7
[0086] Tensile strength / GPa Tensile modulus / GPa Example 1 3.3 480 Example 2 2.5 560 Example 3 3.2 471 Example 4 2.8 510 Example 5 2.4 590 Example 6 3.0 498 Example 7 2.7 521
[0087] It can be seen from Table 1 that the polyacrylonitrile-based carbon fiber prepared in the embodiment of the present invention has a high tensile modulus, good tensile strength and excellent overall mechanical properties.
[0088] Example 8
[0089] 3K polyacrylonitrile-based fiber (comonomers include acrylonitrile, methyl acrylate and itaconic acid) was used. In the pre-oxidation stage, a draft ratio of 4% was applied to the polyacrylonitrile-based fiber. Pre-oxidation was carried out in 6 temperature zones, which were 235°C for 15 min, 245°C for 15 min, 255°C for 15 min, 265°C for 15 min, 275°C for 15 min, and 285°C for 15 min. Low-temperature carbonization was carried out in 4 temperature zones, The method comprises the following steps: keeping the temperature at 390°C for 3.5 min, keeping the temperature at 570°C for 3.5 min, keeping the temperature at 770°C for 3.5 min, and keeping the temperature at 590°C for 3.5 min, with a total stretching ratio of -7%; then high-temperature carbonization is carried out, and the temperature is gradually increased through 4 temperature zones, namely keeping the temperature at 1100°C for 1 min, keeping the temperature at 1300°C for 1 min, keeping the temperature at 1500°C for 1 min, and keeping the temperature at 1700°C for 1 min, with a total stretching ratio of -5%, to obtain polyacrylonitrile-based carbon fiber.
[0090] Example 9
[0091] The preparation method of this embodiment is the same as that of Example 8, except that the holding time of each pre-oxidation stage is 10 minutes, and other conditions are the same as those of Example 8.
[0092] Example 10
[0093] The preparation method of this embodiment is the same as that of Example 8, except that the holding time of each pre-oxidation stage is 12 minutes, and other conditions are the same as those of Example 8.
[0094] Embodiment 11
[0095] The preparation method of this embodiment is the same as that of embodiment 9, except that the holding time of each low-temperature carbonization stage is 3 minutes, and other conditions are the same as those of embodiment 9.
[0096] Example 12
[0097] The preparation method of this embodiment is the same as that of Example 11, except that the holding time of each low-temperature carbonization stage is 4.5 minutes, and other conditions are the same as those of Example 11.
[0098] Example 13
[0099] The preparation method of this embodiment is the same as that of Example 11, except that the total stretching ratio of low-temperature carbonization is -5%, and other conditions are the same as those of Example 11.
[0100] Embodiment 14
[0101] The preparation method of this embodiment is the same as that of embodiment 11, except that the total draft of low temperature carbonization is -3%, and other conditions are the same as those of embodiment 11. The cross section of the obtained polyacrylonitrile-based carbon fiber is as follows: Figure 4 shown.
[0102] Embodiment 15
[0103] The preparation method of this embodiment is the same as that of embodiment 13, except that the holding time of each high-temperature carbonization stage is 2.4 min, and other conditions are the same as those of embodiment 13. The cross-section of the obtained polyacrylonitrile-based carbon fiber is as follows: Figure 3 shown.
[0104] according to Figure 3 and Figure 4 It can be seen that the fracture of polyacrylonitrile-based carbon fiber starts from the defect. The looser the core structure is than the skin, the lower the strength of the polyacrylonitrile-based carbon fiber.
[0105] Example 16
[0106] The preparation method of this embodiment is the same as that of Example 13, except that the holding time of each high-temperature carbonization stage is 1.5 minutes, and other conditions are the same as those of Example 13.
[0107] Embodiment 17
[0108] The preparation method of this embodiment is the same as that of Example 15, except that the total stretching ratio of high-temperature carbonization is -5%, and other conditions are the same as those of Example 15.
[0109] Embodiment 18
[0110] The preparation method of this embodiment is the same as that of Example 15, except that the total stretching ratio of high-temperature carbonization is -1%, and other conditions are the same as those of Example 15.
[0111] Embodiment 19
[0112] The preparation method of this embodiment is the same as that of Example 17, except that 6K polyacrylonitrile-based fiber is used, and other conditions are the same as those of Example 17.
[0113] The tensile strength and tensile modulus of the polyacrylonitrile-based carbon fibers prepared in Examples 8 to 19 were tested according to the GB / T 3362-2017 standard. The results are shown in Table 2.
[0114] Table 2 Tensile strength and tensile modulus of polyacrylonitrile-based carbon fibers of Examples 8 to 19
[0115] Tensile strength / GPa Tensile modulus / GPa Example 8 4.1 220 Example 9 4.6 210 Example 10 3.8 250 Embodiment 11 4.8 240 Example 12 4.5 210 Example 13 5.3 220 Embodiment 14 4.5 260 Embodiment 15 5.8 250 Example 16 5.0 207 Embodiment 17 6.5 220 Embodiment 18 5.4 227 Embodiment 19 5.7 245
[0116] It can be seen from Table 2 that the tensile modulus and tensile strength of the polyacrylonitrile-based carbon fibers prepared in the embodiments of the present invention are relatively high.
[0117] It can be seen from the above embodiments that the polyacrylonitrile-based carbon fiber provided by the present invention has a high tensile modulus of 200 to 590 GPa and good tensile strength of more than 2.4 GPa.
[0118] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing polyacrylonitrile-based carbon fiber, characterized in that: The following steps are involved: The polyacrylonitrile-based fiber is sequentially subjected to pre-oxidation, low-temperature carbonization, alkali leaching, high-temperature carbonization and graphitization to obtain the polyacrylonitrile-based carbon fiber; the temperature of the low-temperature carbonization is 300-800°C; the reagent for the alkali leaching is an aqueous solution of a metal catalyst; the temperature of the high-temperature carbonization is 1200-1500°C; the temperature of the graphitization is 2000-2500°C.
2. The preparation method according to claim 1, characterized in that: The pre-oxidation is a segmented pre-oxidation; the segmented pre-oxidation includes sequentially performing a first pre-oxidation, a second pre-oxidation, a third pre-oxidation, a fourth pre-oxidation, a fifth pre-oxidation and a sixth pre-oxidation; the temperature of the first pre-oxidation is 230-245°C, and the holding time is 10-20 min; the temperature of the second pre-oxidation is 240-255°C, and the holding time is 10-20 min; the temperature of the third pre-oxidation is 250-265°C, and the holding time is 10-20 min; the temperature of the fourth pre-oxidation is 260-275°C, and the holding time is 10-20 min; the temperature of the fifth pre-oxidation is 270-285°C, and the holding time is 10-20 min; the temperature of the sixth pre-oxidation is 280-295°C, and the holding time is 10-20 min; the total stretching ratio of the pre-oxidation is 2-8%.
3. The preparation method according to claim 2, characterized in that: The temperature of the first pre-oxidation is 230-240°C; the temperature of the second pre-oxidation is 240-250°C; the temperature of the third pre-oxidation is 250-260°C; the temperature of the fourth pre-oxidation is 260-270°C; the temperature of the fifth pre-oxidation is 270-280°C; the temperature of the sixth pre-oxidation is 280-295°C; and the total stretching ratio of the pre-oxidation is 2-6%.
4. The preparation method according to claim 1, characterized in that: The low-temperature carbonization is segmented low-temperature carbonization; the segmented low-temperature carbonization includes sequentially performing a first low-temperature carbonization, a second low-temperature carbonization, a third low-temperature carbonization and a fourth low-temperature carbonization; the temperature of the first low-temperature carbonization is 300-400°C, and the heat preservation carbonization time is 3-5 min; the temperature of the second low-temperature carbonization is 500-600°C, and the heat preservation carbonization time is 3-5 min; the temperature of the third low-temperature carbonization is 600-800°C, and the heat preservation carbonization time is 3-5 min; the temperature of the fourth low-temperature carbonization is 500-600°C, and the heat preservation carbonization time is 3-5 min; the total stretching ratio of the low-temperature carbonization is -7 to -1%.
5. The preparation method according to claim 4, characterized in that: The temperature of the first low-temperature carbonization is 380-400°C; the temperature of the second low-temperature carbonization is 550-600°C; the temperature of the third low-temperature carbonization is 750-800°C; and the temperature of the fourth low-temperature carbonization is 580-600°C.
6. The preparation method according to claim 1, characterized in that: The high-temperature carbonization is segmented high-temperature carbonization; the segmented high-temperature carbonization includes sequentially performing a first high-temperature carbonization and a second high-temperature carbonization; the temperature of the first high-temperature carbonization is 1200-1300°C, and the insulation time is 1-4 minutes; the temperature of the second high-temperature carbonization is 1300-1600°C, and the insulation time is 1-4 minutes; the total stretching ratio of the high-temperature carbonization is -5-1%.
7. The preparation method according to claim 1, characterized in that: The high-temperature carbonization is a four-stage high-temperature carbonization; the four-stage high-temperature carbonization includes a third high-temperature carbonization, a fourth high-temperature carbonization, a fifth high-temperature carbonization and a sixth high-temperature carbonization in sequence; the temperature of the third high-temperature carbonization is 1000-1200°C, and the heat preservation carbonization time is 1-2.5min; the temperature of the fourth high-temperature carbonization is 1200-1400°C, and the heat preservation carbonization time is 1-2.5min; the temperature of the fifth high-temperature carbonization is 1400-1600°C, and the heat preservation carbonization time is 1-2.5min; the temperature of the sixth high-temperature carbonization is 1600-1800°C, and the heat preservation carbonization time is 1-2.5min; the total drawing ratio of the four-stage high-temperature carbonization is -7-0.5%.
8. The preparation method according to claim 1, characterized in that: The graphitization includes a first graphitization and a second graphitization performed sequentially; the temperature of the first graphitization is 2000-2200° C., and the insulation graphitization time is 10-85 seconds; the temperature of the second graphitization is 2300-2500° C., and the insulation graphitization time is 10-135 seconds; the total stretching ratio of the graphitization is -1-7%.
9. The polyacrylonitrile-based carbon fiber obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the polyacrylonitrile-based carbon fiber according to claim 9 in the fields of aerospace, automotive materials, sports equipment or wind power generation.
Citation Information
Cited By
PI / PAN coaxial composite-based carbon fiber as well as preparation method and application thereof
CN120366930A
